The complete mitogenome of freshwater gammarid Grandidierella taihuensis (Crustacea: Amphipoda). Issue 4 (3rd April 2021) - Yin, Jiawen; Zhao, Muzi; Zhang, Zeng; Fu, Yanyan; Liu, Yanshan; Liu, Xiaowei; Xu, Junhua; Gui, Zeyu; Tang, Shengkai; Zhang, Tongqing
Abstract: The freshwater gammarid Grandidierella taihuensis is an important composition of benthic community. In this study, the complete mitogenome sequences of G. taihuensis are determined using next-generation and PacBio long-read sequencing. The mitogenome of G. taihuensis is 15, 099 bp in size, and consisted of 13 protein-coding genes, two ribosomal RNA genes, 22 tRNA genes, and a putative control region. Gene arrangement is as same as that of G. rubroantennata . The base composition of the entire mitogenome showed a conspicuous A + T bias of 69.4%. The mitogenome data produced in this study provides a useful resource for future evolutionary and ecological studies.